2018
DOI: 10.1002/jcb.26431
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐103 confers the resistance to long‐treatment of adriamycin to human leukemia cells by regulation of COP1

Abstract: Adriamycin (ADR) is an anti-cancer drug which offers improvement in survival for acute myeloid leukemia (AML) patients. However, the drug resistance is almost inevitable. Increasing evidences suggested that microRNAs (miRNAs) were associated with cancer chemo-resistance. Here, we aimed to explore the possible mechanism of miR-103 affected resistance to ADR in AML cells. Different concentrations of ADR were used to induce K562 and KASUMI-1 cells, and miR-103 mimic, inhibitor were transfected into K562 and KASUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…WNT/β-catenin, RAS/ERK/ MAPK, JAK/STAT, NOTCH), we believe ncRNA may also play a role in the resistance of PI3K inhibitors [194][195][196][197][198][199]. Not surprisingly, more and more researches have suggested that deviant ncRNA expression is powerfully concerned about tumor drug resistance [200][201][202][203][204][205][206][207][208]. Recent studies have indicated potential mechanism of acquired resistance to dual PI3K/mTOR inhibitors, including elevated glycolysis accompanied with depletion of mitochondrial DNA, and upregulated DNA methyltransferases which Reduce PTEN and PPP2R2B expression [209,210].…”
Section: Resistancesmentioning
confidence: 99%
“…WNT/β-catenin, RAS/ERK/ MAPK, JAK/STAT, NOTCH), we believe ncRNA may also play a role in the resistance of PI3K inhibitors [194][195][196][197][198][199]. Not surprisingly, more and more researches have suggested that deviant ncRNA expression is powerfully concerned about tumor drug resistance [200][201][202][203][204][205][206][207][208]. Recent studies have indicated potential mechanism of acquired resistance to dual PI3K/mTOR inhibitors, including elevated glycolysis accompanied with depletion of mitochondrial DNA, and upregulated DNA methyltransferases which Reduce PTEN and PPP2R2B expression [209,210].…”
Section: Resistancesmentioning
confidence: 99%
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%
“…Upregulation of miR-103 was found by Yefenof et al, to sensitize leukemia cells to glucocorticoids ( 50 ). However, a study by Zhang et al, showed that miR-103 is upregulated in adriamycin-resistant cells ( 51 ). miR-486-3p could act as a tumor-suppressive miRNA in several cancers ( 52 54 ).…”
Section: Discussionmentioning
confidence: 99%